First Detection of Mukawa Virus in Ixodes persulcatus and Haemaphysalis concinna in China - Wang, Yu-Na; Jiang, Rui-Ruo; Ding, Heng; Zhang, Xiao-Long; Wang, Ning; Zhang, Yun-Fa; Li, Yue; Chen, Jin-Jin; Zhang, Pan-He; Li, Hao; Jiang, Jia-Fu; Liu, Lan-Zheng; et al. (Frontiers in Microbiology, 2022)
Abstract: Mukawa virus (MKWV), a novel tick-borne virus (TBV) of the genus Phlebovirus of family Phenuiviridae, has been firstly reported in Ixodes persulcatus in Japan. In this study, we made an epidemiological investigation in China to obtain the geographic distribution and genetic features of this virus outside Japan. We screened 1815 adult ticks (665 I.persulcatus, 336 Dermacentor silvarum, 599 Haemaphysalis longicornis, 170 Rhipicephalus microplus, 45 Haemaphysalis concinna) and 805 wild small mammals collected from eight provinces. The positive rate of 6.77% (45/665, including 18 female and 27 male I.persulcatus) and 2.22% (1/45, 1 male H. concinna) were obtained from I.persulcatus and H. concinna in Heilongjiang province, respectively. No evidence of MKWV infection was found in other three tick species or any of the mammalian species. The virus can infect the Vero cells successfully, indicating the ability of MKWV to replicate in mammalian cells. Phylogenetic tree based on the nucleotide sequences of L, M, and S segments, demonstrated that the Japanese MKWV variant, our two MKWV variants, and KURV clustered with the members of the mosquito/sandfly-borne phleboviruses and distant from other tick-borne phenuiviruses. Phylogenetic analysis based on 895 bp partial L gene sequences (n=46) showed that all MKWV sequences were separated into three lineages. Our results showed the presence of MKWV in I. persulcatus and H. concinna in northeast of China, highlighting the necessity of epidemiological study in wider regions. Due to the ability of MKWV to replicate in mammalian cells, the potential for zoonosis, and wide distribution of I. persulcatus and H. concinna in China, the important vectors of MKWV, further screening to more tick species, wild animals, domestic animals and human raise up practical significance. Keywords: ticks, tick-borne phlebovirus, Ixodes persulcatus, Haemaphysalis concinna, China